Outcome of Soybean Dregs and Cassava Addition towards Synthetic Chicken Meat Texture and Nutrition - Dewi Tristantini; Tiara Febriani; Monica Winata (Seminar Nasional Teknik Kimia Kejuangan, 2016)
Meat is one of the main sources of protein that society enjoys consuming, particularly chicken. However, meat may be unhealthy and cause excessive cholesterol, diabetes, and weight gain, also pathogenic such as avian influenza. Meat alternative that is healthier is synthetic meat. Synthetic meat is created from organic ingredients with protein content that resembles meat. Protein in synthetic meat is obtained from ingredients such as gluten, soybean dregs, and cassava. Aside from protein, other nutrition such as fiber, carbohydrate, fats, and minerals are also incorporated in synthetic meat. In manufacturing synthetic meat, the concentration of soybean dregs and cassava are varied in order to observe the effect from both ingredients towards nutrition and texture. Synthetic meat will be analyzed proximately, calorimetrically, its texture by texture profile analysis (TPA) and scanning electron microscopy (SEM), shelf life, and amino acids. From this research, a formulation for synthetic chicken meat is obtained based on its nutrition and texture. The best composition for synthetic chicken meat consists of 60% gluten, 5% cassava, and 20% soybean dregs.